PERSEPSI GURU TERHADAP PROGRAM SERTIFIKASI GURU - Atiek Winarti (QUANTUM: Jurnal Inovasi Pendidikan Sains, 2010)
Abstract: This research analyzes teachers’ perception towards the implementation of Teacher Certification Program (TCP) conducted in Indonesia. Next to that, the differences in teachers’ perception between certified and uncertified teachers were also discussed to find whether the difference perception between certified and uncertified teachers exists. To obtain such objectives, a comparative survey research was established. Of 99 randomly selected sample of senior high school teachers in Banjarmasin municipality of South Kalimantan Province of Indonesia who did not follow TCP, failed and passed on portfolio assessment were included in the study. The data was gathered by using a close ended questionnaire with 5 subscales . The descriptive analysis of teachers’ perception of total-TCP- and TCP-subscales showed that teachers have a positive perception of the implementation of TCP. Data analyze by Anova and Kruskal Wallis test showed that no significant differences in teachers perception between three groups of teachers. Besides, teachers gave some positive suggestions for improving the implementation of TCP.Key words: teachers’ perception, teacher certification program, teacher quality.